Disruptive School Peers and Student Outcomes - Jannie H. G. Kristoffersen; Morten Visby Kraegpøth; Helena Skyt Nielsen; Marianne Simonsen (Institute for the Study of Labor (IZA), 2015)
This paper estimates how peers' achievement gains are affected by the presence of potentially disruptive and emotionally sensitive children in the school-cohort. We exploit that some children move between schools and thus generate variation in peer composition in the receiving school-cohort. We identify three groups of potentially disruptive and emotionally sensitive children from detailed Danish register data: children with divorced parents, children with parents convicted of crime, and children with a psychiatric diagnosis. We find that adding potentially disruptive children lowers the academic achievement of peers by about 1.7-2.3 percent of a standard deviation.
Keywords: I21; J12; 330; student mobility; special educational needs; education; value added model